2016
DOI: 10.1111/myc.12504
|View full text |Cite
|
Sign up to set email alerts
|

Non‐dermatophytic onychomycosis diagnostic criteria: an unresolved question

Abstract: Non-dermatophytic moulds (NDMs) have been increasingly recognised as causative agents of onychomycosis. The diagnosis of onychomycosis is most often obtained by microscopic observation of nail specimens where fungal elements can be detected and cultured by standard mycological techniques. Direct microscopic examination does not always result positive in NDM onychomycosis; therefore to perform a correct diagnosis, a proper mycological culture is often required. The purpose of our study was to evaluate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The remaining dermatophyte infections are caused by Epidermophyton floccosum , Microsporum species, Trichophyton verrucosum , Trichophyton tonsurans , Trichophyton violaceum , Trichophyton soundanense , Trichophyton krajdenii , Trichophyton equinum , and Arthroderma species [ 13 - 17 ]. Non-dermatophyte molds that can cause onychomycosis include Aspergillus species, Scopulariopsis species, Fusarium species, Acremonium species, Syncephalastrum species, Scytalidium species, Paecilomyces species, Neoscytalidium species, Chaetomium species, Onychocola species, and Alternaria species [ 11 , 17 , 18 - 31 ]. Non-dermatophyte molds account for approximately 10% of onychomycosis cases globally [ 6 , 32 ].…”
Section: Etiologymentioning
confidence: 99%
“…The remaining dermatophyte infections are caused by Epidermophyton floccosum , Microsporum species, Trichophyton verrucosum , Trichophyton tonsurans , Trichophyton violaceum , Trichophyton soundanense , Trichophyton krajdenii , Trichophyton equinum , and Arthroderma species [ 13 - 17 ]. Non-dermatophyte molds that can cause onychomycosis include Aspergillus species, Scopulariopsis species, Fusarium species, Acremonium species, Syncephalastrum species, Scytalidium species, Paecilomyces species, Neoscytalidium species, Chaetomium species, Onychocola species, and Alternaria species [ 11 , 17 , 18 - 31 ]. Non-dermatophyte molds account for approximately 10% of onychomycosis cases globally [ 6 , 32 ].…”
Section: Etiologymentioning
confidence: 99%
“…17 In an additional study, 42.8% of nondermatophyte moulds (NDM) onychomycosis patients (N = 35) were negative for microscopy but positive in 3 or more subsequent cultures. 18 This large proportion of false negatives could be the result of disease duration differences or the skill level of the technician. 18 The sensitivity of direct microscopy can be enhanced when combined with culture or histology testing, increasing sensitivity rates from 48% to 74% and 89%, respectively.…”
Section: Microscopymentioning
confidence: 99%
“…18 This large proportion of false negatives could be the result of disease duration differences or the skill level of the technician. 18 The sensitivity of direct microscopy can be enhanced when combined with culture or histology testing, increasing sensitivity rates from 48% to 74% and 89%, respectively. 17 It is therefore recommended that microscopic examination is used with repeated isolations and identification across several subsequent cultures.…”
Section: Microscopymentioning
confidence: 99%
“…Interestingly, the direct microscopic examination of non-dermatophyte mold onychomycosis has been shown to yield a high false negative result of more than 42%. 3 In addition, a recent meta-analysis concluded that the accuracy of KOH and cultures was lower compared to nail biopsy with Periodic Acid-Schiff (PAS)-staining, 4 something worth considering in patients with recalcitrant onychomycosis.…”
Section: Discussionmentioning
confidence: 99%